Penciptaan Keramik Kitchen Set Kolaborasi Dengan Ud. Tri Surya Keramik: Kreamik Kreasi - Adi Gunawan I Made; Muka I Ketut; Rai Sunarini Ni Made (Pusat Penerbitan LPPM ISI Bali, 2026)
Balinese ceramic crafts are a cultural heritage rich in artistic and religious values, but face sustainability challenges due to the declining interest of the younger generation. This research aims to study the process of making ceramics with the electric wheel technique at UD. Tri Surya Keramik, Badung Regency, Bali, and develop ceramic products with local cultural nuances to meet tourism needs, especially kitchen sets and decorations. The methods used include active participation, observation, interviews, and literature study to understand the stages of production, starting from clay processing, forming, decorating, glazing, to firing. The learning process at UD. Tri Surya Keramik includes systematic stages such as clay processing through drying, pounding, sifting, and kneading to ensure a plastic texture, forming with electric wheel techniques to produce symmetrical shapes such as cylinders, vases, bowls, and plates, decorating with incised techniques, glazing with dip or spray techniques, and firing biscuits (800-900°C) and glaze (1,200-1,250°C). The aesthetics of decoration on ceramic products reflect Balinese culture through incised and cukil techniques that produce carved patterns with natural nuances, such as leaf motifs and curved lines, which add artistic value and local identity. The results showed that the learning process at UD. Tri Surya Keramik produces functional and decorative products, such as tableware and vases, with high quality that combine traditional Balinese aesthetics and modern market needs. The products exhibit symmetry, surface smoothness, and glaze color harmony, with great potential to improve competitiveness through design innovation. This research also provides insight into the importance of collaboration between industry and education to preserve and develop ceramic crafts, while encouraging the younger generation's interest in local ceramic art.